The effectiveness of alitretinoin for the treatment of chronic hand eczema: A meta-analysis - Al-Dhubaibi, Mohammed Saleh; Settin, Ahmed Abdusalam (International Journal of Health Sciences, 2018)
Alitretinoin is a new oral retinoid authorized for use in grownups that have severe chronic hand eczema (CHE). A comprehensive search to solicit all studies of alitretinoin for the treatment of CHE. A comprehensive search to solicit all studies of alitretinoin for the treatment of CHE including randomized controlled trials (RCTs) or uncontrolled trials, re-treatment studies, open-label studies, or observational studies, along with case series of 10 or more participants. Physician global assessment (PGA), patient global assessment (PaGA) and modified total lesion symptom score (mTLSS) are the methods and outcomes criteria. Generated effect size and 95% confidence intervals were calculated for the outcomes. Heterogeneity and publication bias were also tested for all selected trials. When a noteworthy Q statistic (P < 0.1) demonstrates the heterogeneity crosswise over studies, an arbitrary impact model is used. On the other hand, a settled effect model is when heterogeneity is not shown. The initial search yielded 408 records of which 15 articles were selected. The 15 clinical trials included 3734 patients with CHE. Among alitretinoin-treated patients, the PGA effect size was directly proportional to the drug dosage, ranging from 40% to 69%, while the PaGA score ranged from 28.8% to 62.4%, and mTLSS ranged from 60.4% to 76.9%, much higher than placebo. A higher drug dose was about twice as effective as lower dose. The odds ratio for a better outcome with drug treatment taking duration into account was about 3–4 times that versus placebo. In conclusions, alitretinoin cleared lesions in about 50% of cases, particularly using a higher dose for a longer duration.